DETERMINANTS OF SOCIAL ESTABLISHMENT OF ATTITUDE OF EMPATHY VII CLASS STUDENTS - vina wijaya; Berchah Pitoewas; yunisca nurmalisa (Jurnal Kultur Demokrasi, 2012)
The purpose of this research is to discover and explain the factors determining the formation of social empathy among students of SMP Negeri 1 Abung North West Lampung school year 2012/2013. This research uses descriptive method, the subject under study is a class VII student of SMP Negeri 1 West Abung learners totaling 240 people. Samples taken 10% or 24 students. Data collection used was a questionnaire, which is supported by interviews and documentation. While to analyze the data using a percentage formula. The results that the internal factors determining the formation of social empathy among students of SMP Negeri 1 Abung North West Lampung regency school year 2012/2013 based on calculations at the high category as much as 70.83%, external factors determining the formation of a family social empathy in students is the category of being as much as 50%, external factors determining the formation of peer social empathy in class VII student at West Junior High School 1 Abung school year 2012/2013 at the high category as much as 66.76%. This suggests that intense and external factors determining the formation of social empathy class VII student at West Junior High School 1 Abung North Lampung Academic Year 2012/2013.Keywords: Social Empath